Analisis Pelaksanaan Pemungutan Pajak Restoran Dalam Rangka Meningkatkan Pendapatan Asli Daerah (PAD) Kabupaten Klaten - Hidayah, Anisa Nurul; Dewi, Maya Widyana; Kristiyanti, LMS (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to analyze the implementation of restaurant tax collection in Klaten Regency and to assess its growth rate and contribution to Regional Original Revenue (PAD). The research employed a descriptive approach with a combination of qualitative and quantitative methods. Primary data were obtained through interviews with BPKAD officers and restaurant taxpayers, while secondary data were drawn from tax realization reports for 2018–2022. Qualitative analysis followed the Miles, Huberman, & Saldaña model, whereas quantitative analysis included the calculation of growth rates and tax contributions. The findings reveal that restaurant tax collection has been implemented under the self-assessment system; however, taxpayer compliance remains low, field supervision is limited, and negative perceptions of tax benefits are prevalent. Quantitatively, restaurant tax growth was fluctuating and classified as less successful, while its contribution to PAD remained in the low to moderate category (1.23%–2.29%). The study highlights the need to enhance tax literacy, strengthen institutional capacity, and enforce consistent regulations so that restaurant tax can more optimally support regional fiscal independence.